2013
DOI: 10.1007/s10198-013-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

Equity in specialist waiting times by socioeconomic groups: evidence from Spain

Abstract: In countries with publicly financed health care systems, waiting time--rather than price--is the rationing mechanism for access to health care services. The normative statement underlying such a rationing device is that patients should wait according to need and irrespective of socioeconomic status or other non-need characteristics. The aim of this paper is to test empirically that waiting times for publicly funded specialist care do not depend on patients' socioeconomic status. Waiting times for specialist ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
3
23
0
6
Order By: Relevance
“…In the United States, twelve percent of patients belonging to managed care plans reported that it was difficult to get the specialist referrals they needed, leading to lower ratings of trust, confidence and satisfaction with the PCP [51]. Particularly Spanish individuals belonging to lower socioeconomic groups might be affected by the PCP’s unfavourable referral pattern [52] and should hence be paid special attention so that their health needs are met.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, twelve percent of patients belonging to managed care plans reported that it was difficult to get the specialist referrals they needed, leading to lower ratings of trust, confidence and satisfaction with the PCP [51]. Particularly Spanish individuals belonging to lower socioeconomic groups might be affected by the PCP’s unfavourable referral pattern [52] and should hence be paid special attention so that their health needs are met.…”
Section: Discussionmentioning
confidence: 99%
“…Este resultado pode indicar igualdade de acesso ao serviço público independentemente do nível de escolaridade, o que é um bom indicador de qualidade. Na Espanha, os pacientes com menores níveis de educação esperam mais tempo pela consulta especializada do que os mais instruídos (17) .…”
Section: Discussionunclassified
“…Verificou-se, ainda, que os participantes com renda superior ao salário mínimo vigente no país esperaram menos tempo pela consulta dermatológica do que os de renda igual ou inferior a um salário mínimo, tendo sido esta diferença estatisticamente significante. Este resultado foi semelhante ao encontrado em um estudo da Espanha, que mostra que os pacientes com menores níveis de renda esperam mais por atendimentos especializados (17) . Porém, como o p-valor foi próximo a 0,05, são recomendados mais estudos para avaliação deste dado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dear Editor , Accessibility and waiting times represent a general problem in public‐financed healthcare systems . The Italian National Health Service (NHS) provides free healthcare access to every Italian citizen, and is funded through direct and indirect taxation.…”
mentioning
confidence: 99%